1978
DOI: 10.1002/zaac.19784400112
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Röntgenstrukturanalyse des Additionsproduktes von Schwefeltrioxid an Tetraschwefeltetranitrid (S4N4· SO3)

Abstract: S4N4 · SO3 wurde durch Reaktion von S4N4 mit SO3 in CH2Cl2 und über eine lösungsmittelfreie Umsetzung von S4N4 mit Fluorsulfonsäureanhydrid erhalten. Eine Einkristall‐Röntgen‐Strukturanalyse lieferte die Struktur des Adduktes. Der „Käfig”︁ des freien S4N4 faltet analog der Struktur des S4N4 · SbCl5 in eine deformierte Sattelkonformation mit näherungsweise Cs‐Symmetrie um. Die SN‐Bindungsabstände im S4N4‐Ring Variieren von 1,51 bis 1,69 Å. Die Cs‐Symmetrie wird deutlich durch die Stellung der SO3‐Gruppe durchb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
(1 reference statement)
1
18
0
5
Order By: Relevance
“…However, the number of other known tellurium tetrahalide adducts containing a Te-N bond is sparse. Gieren et al [12] have reported the crystal structure of TeF 4 (NNCHCHCH) 2 and Massa et al [13] have determined that of [Te 6 N 8 (TeCl 4 ) 4 ]·4THF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the number of other known tellurium tetrahalide adducts containing a Te-N bond is sparse. Gieren et al [12] have reported the crystal structure of TeF 4 (NNCHCHCH) 2 and Massa et al [13] have determined that of [Te 6 N 8 (TeCl 4 ) 4 ]·4THF.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures are known for BF 3 ·S 4 N 4 , [1] SO 3 ·S 4 N 4 , [2] AsF 5 ·S 4 N 4 , [3] SbCl 5 ·S 4 N 4 , [4][5][6] FeCl 3 ·S 4 N 4 , [7,8] TaCl 5 ·S 4 N 4 , [9] and TiCl 4 ·S 4 N 4 . [10] The complexes SnCl 4 ·2S 4 N 4 [11] and TiCl 4 ·2S 4 N 4 [10] exemplify structurally characterized adducts with a 1:2 stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecule of the S4N4.AsF 5 adduct has crystallographic mirror symmetry and is very similar to the molecules of the 1:1 adducts of S4N 4 with BF 3 (Drew, Templeton & Zalkin, 1967), SbCl 5 (Neubauer & Weiss, 1960, SO 3 (Gieren, Dederer, Roesky, Amin & Petersen, 1978) and FSO2NCO (Gieren, Hahn, Dederer, Roesky & Amin, 1978), although it differs significantly from that of the adduct with CuCl (Thewalt, 1976). In all of the former compounds the S4N 4 ring has a modified saddle conformation with the four S atoms in a plane, and the Lewis acid coordinated to a N atom.…”
Section: Discussionmentioning
confidence: 78%
“…1 kristallisiert aus Methylenchlorid in der monoklinen Raumgruppe P2,/c mit 4 Molekiilen pro Elementarzelle (1 Molekiil pro asymm. Einheit) und den folgenden Gitterkonstanten: u = 797.…”
Section: Rontgenanalyseunclassified